Performance of a photon conversion trigger in proton-proton collisions using the ALICE Transition Radiation Detector - Barreiros, Andre S (Department of Physics, 2023)
The study aimed to find the yield of conversion photons in pp √ s = 13 TeV with less uncertainty for high transverse momentum photons through the TRD in ALICE (necessary for π 0 and η cross-sections). The calculation of the yield of conversion photons were successful in replicating their yield from minimum bias data set. During this process it was detected that the TRD trigger formed a smaller data set within the minimum bias than was hoped for, leading to high uncertainties. To remedy the trigger efficiency uncertainties, a Monte Carlo simulation of LHC18o, LHC18k2, was proposed to supplement the lack of statistics in the data. The TRD trigger was replicated within the MC data set, allowing for the comparison of relative cut efficiencies between the two data sets. This enabled the further identification of discrepancies between the data set, limiting its use for the TRD. The various discrepancies detected were: i) differences in the sagitta values of the TRD tracks; ii) particles from photon conversions are about 10% more likely to find a corresponding TRD track in MC; iii) HQU (Quarkonium) trigger cuts had varying relative efficiency for conversion photons between data sets; iv) the deflections of TRD tracklets differed by about 0.176 mm. Discrepancy ii) can be halved by limiting pile-up photons. Charged particles with pT > 2 GeV/c from the primary vertex are well simulated within the TRD. In relation to point iv). the difference in deflection seems to be too small to affect TRD trigger efficiency and should be remedied. The MC seems to have the most problems in simulating late conversion, low transverse momentum tracks. As a result, conversion photons are not well simulated in the MC.